MERCHANDISE TRADE IN THE EAEU INTEGRATING ENVIRONMENT - Hrechyshkina, Olena; Samakhavets, Maryia (Quaestiones Geographicae, 2019)
The paper aims to identify the main trends and recommendations for the development of merchandise trade in the Eurasian Economic Union (EAEU) integrating environment through the analysis of its mutual and foreign (internal and external) merchandise trade. The study is based on the official statistical data for 2014–2018 and economic comparisons and systematisation (including geographical systematisation). The results show that the intensification of mutual and foreign trade in the EAEU is possible by stimulating consumer and industrial demand, enhancing exports of high tech products and diversifying exports, and strengthening the cooperation within the EAEU and with other countries and integration associations.